Acellular Dermal Matrix Performance Compared with Latissimus Dorsi Myocutaneous Flap in Expander-Based Breast Reconstruction. Issue 9 (September 2019) - Patrinely, James Randall; Farinas, Angel; Al-Majed, Bader; Forte, Antonio Jorge; TerKonda, Sarvam; Perdikis, Galen
Abstract : Background: Latissimus dorsi myocutaneous flap (LDMF) with tissue expander provides excellent results in breast reconstruction. Acellular dermal matrix (ADM) has been used in expander-based reconstruction (EBR) with good results. This study assesses how ADM compares to LDMF in EBR. Methods: The cohorts comprised 124 patients (218 breasts) who had EBR using ADM between 2006 and 2012, and 242 patients (266 breasts) who had EBR using LDMF between 1994 and 2012. Postoperative complications, reoperations, Breast-Q scores, and objectively assessed aesthetic outcomes were compared. Results: Median age was 55 years for both ADM (range 23–84) and LDMF (range 26–88) groups. No statistically significant differences were noted between the groups in the rates of major postoperative complications ( P > 0.3). Forty-nine of the 218 (22.5%) in the ADM group and 67 of 266 (25.2%) in the LDMF group had a total of 63 and 84 reoperations, respectively ( P = 0.52), with no significant differences in the reoperations rate ( P > 0.3). No significant differences were observed in the Breast-Q scores. Some categorical differences were noted in the aesthetic outcomes; however, the difference between the overall outcomes was not significant ( P = 0.54). Conclusion: Our study revealed no statistically significant differences in the complications or reoperation rates, patient satisfaction, or overall aesthetic outcomes when comparing the use of ADM to LDMF in EBR. In conclusion, this study supports the hypothesis that ADM performs as well as LDMF in EBR.